"Jing-Ning Granules" Can Alleviate Attention Deficit Hyperactivity Disorder in Rats by Modulating Dopaminergic D2/D1-Like Receptor-Mediated Signaling Pathways. (28th October 2022) - Ding, Jie; Ding, Yiyun; Wu, Jingjing; Deng, Jialin; Yu, Qingyang; Wang, Junhong
Abstract : Background . Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder characterized by attention deficit, hyperactivity, and impulsivity. Jing-Ning Granules (JNG) is a traditional Chinese medicine (TCM) that can alleviate ADHD. Although JNG is commonly used for the effective treatment of ADHD and has obtained the national invention patent, the exact mechanism of action remains unclear. Objective . In this study, we examined the effect and mechanism of JNG in spontaneously hypertensive rats (SHRs). We hypothesized that JNG affects dopaminergic D2/D1-like receptors and related pathways. Materials and Methods . Six rat groups were used in the experiment: Wistar-Kyoto rats (WKY, control group) and five SHR groups, including a model group; atomoxetine (ATX, positive control) group; and low, medium, and high-dose JNG groups. The corresponding treatments were daily administered to each group for 6 weeks. A behavioral test, including a step-down test and open field test (OFT), was carried out at the end of treatment. After the behavioral test, all animals were sacrificed, and the brain tissue was collected and analyzed ex vivo; histopathological analysis was performed to assess the pathological changes of the hippocampus; expression of D1-like and D2-like receptors, sensor protein calmodulin (CaM), protein kinase A (PKA), and calcium/calmodulin-dependent serine/threonine protein kinase (CaMKII) in the striatum and hippocampus was measured by western blot and real-time quantitative PCR (RT-PCR); cyclic adenosine monophosphate (cAMP) levels in the striatum were analyzed using an enzyme-linked immunosorbent assay (ELISA), while the level of Ca 2+ in the striatum was analyzed by a calcium kit. Results . Our results showed that ATX or JNG could ameliorate the hyperactive/impulsive behavior and cognitive function of ADHD by promoting neuroprotection. Mechanistically, ATX or JNG could prompt the expressions of Dl-like and D2-like receptors and improve the mRNA and protein levels of cAMP/PKA and Ca 2+ /CAM/CAMKII signaling pathways. Conclusion . These results indicate that JNG can produce therapeutic effects by regulating the balance of D2/D1-like receptor-mediated cAMP/PKA and Ca 2+ /CaM/CaMKII signaling pathways.